IMPLICATIONS OF PARENTING STYLES ON STUDENTS' CRITICAL THINKING ABILITIES - Safira Yasira; Nur Rochim Maksum (Universitas Al-Hikmah Indonesia, 2023)
One factor in students' critical thinking abilities is the support of parents who understand and are able to know about differences in status. Parents' parenting style also influences children's thinking abilities. Children's abilities are unlimited, and therefore, age-appropriate education is needed to help identify and develop children's potential. The aim of this research is to understand the implications of parental parenting styles for the development of students' critical thinking. This research uses descriptive qualitative methods and semi-structured interviews. The informants used were early childhood children. Data analysis used in qualitative research is data collection, data processing, and feedback. The results of this research show that there are implications of parental parenting style for students' critical thinking. Students with democratic parenting have higher critical thinking skills than students with authoritarian and permissive parenting styles. Shows that with a democratic parenting style parents have high levels of critical thinking. Because democratic parenting provides a parenting style that respects children's freedom, although parents still provide guidance and attention during its implementation.